Exploitative data harvesting as an article 102 TFEU violation - Vadehra, A (2021)
The digital landscape has become an intrinsic part of our day-to-day lives and has brought numerous benefits to society. A key factor which has enabled such digital (and societal) transformation is big data and platforms’ enhanced abilities to harvest, analyse and use the same. However, despite the distinct benefits provided by big data and analytics, some harmful implications, including in the competition law sphere are notable. Various aspects of such harm are relevant from an antitrust perspective - this thesis focuses on exploitative data collection by dominant platforms and its privacy-degrading implications.